Coronavirus 2 (SARS-CoV-2) in water environments: Current status, challenges and research opportunities. (February 2021) - Ihsanullah, Ihsanullah; Bilal, Muhammad; Naushad, Mu.
Graphical abstract: Highlights: Literature reporting the presence of SARS-CoV-2 in wastewater is reviewed. Evaluation of SARS-CoV-2 in water is vital for its detection and quantification. Research opportunities in water research associated with COVID-19 are highlighted. Favourable environment for the survival of SARS-CoV-2 in water need to be assessed. Effective methods for the removal of SARS-CoV-2 from water need to be developed. Abstract: The outbreak of COVID-19 has posed enormous health, social, environmental and economic challenges to the entire human population. Nevertheless, it provides an opportunity for extensive research in various fields to evaluate the fate of the crisis and combat it. The apparent need for imperative research in the biological and medical field is the focus of researchers and scientists worldwide. However, there are some new challenges and research opportunities in the field of water and wastewater treatment concerning the novel coronavirus 2 (SARS-CoV-2). This article briefly summarizes the latest literature reporting the presence of SARS-CoV-2 in water and wastewater/sewage. Furthermore, it highlights the challenges, potential opportunities and research directions in the water and wastewater treatment field. Some of the significant challenges and research opportunities are the development of standard techniques for the detection and quantification of SARS-CoV-2 in the water phase, assessment of favorable environments for its survival and decay in water; and development of effective strategies for elimination of the novel virus from water. Advancement in research in this domain will help to protect the environment, human health, and managing this type of pandemic in the future.